(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to investigate the extent to which King Faisal University relies on sensory marketing strategies to promote its visual identity and to evaluate the level of integration of these strategies within the marketing and public relations plans being used. The study also seeks to identify the dimensions of using sensory marketing in promoting visual identity and explore the challenges facing its implementation, in addition to determining the activities in which sensory marketing strategies are employed. The study adopts a descriptive approach, focusing on describing and analyzing the relationships between the variables, with a case study methodology used to achieve a deeper understanding of the objectives. A questionnaire was distributed electronically to public relations practitioners at King Faisal University, in addition to conducting interviews with some employees from the University’s Department of Relations and Media. The study population was defined as public relations practitioners at the university, with a selected sample of 13 employees from the Department of Public Relations. The results showed a strong tendency among public relations employees to employ sensory marketing strategies with the aim of enhancing the university’s identity. The use of tangible products such as trophies was suggested as a means to attract the audience’s attention and create a positive emotional connection. The results also highlighted the importance of various activities, such as national celebrations and special events, in strengthening the university’s visual identity. Despite the clear interest in sensory marketing, the actual implementation remains limited, which underscores the need for a clear strategic plan. Observed challenges include budget constraints and limited available resources, as well as weak coordination between different departments. It was also found that the visual dimension is the most influential in enhancing the visual identity, followed by auditory dimensions, while the use of other dimensions (touch, taste, and smell) remains limited. Recommendations include expanding the use of sensory marketing strategies through the development of a clear action plan that focuses on effective sensory dimensions, enhancing coordination among departments, and establishing a specialized unit for sensory marketing. It is also advised to utilize digital platforms and develop effective measurement mechanisms to assess the success of marketing activities. Improving communication with the audience and facilitating interactive events are fundamental elements that will contribute to enhancing King Faisal University’s visual identity, reflecting the importance of these strategies in improving the academic experience and strengthening the connection with the university.